2004
DOI: 10.1099/ijs.0.02911-0
|View full text |Cite
|
Sign up to set email alerts
|

Saccharibacter floricola gen. nov., sp. nov., a novel osmophilic acetic acid bacterium isolated from pollen

Abstract: Three Gram-negative, aerobic, rod-shaped bacterial strains were isolated, from the pollen of Japanese flowers, as producers of xylitol; these strains were subjected to a polyphasic taxonomic study. Phylogenetic analyses of the 16S rRNA gene sequences demonstrated that these three isolates formed a new cluster within a group of acetic acid bacteria in the α-Proteobacteria. The characteristics of the three isolates were as follows: (i) their predominant quinone was Q-10; (ii) their cellular fatty acid profile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(56 citation statements)
references
References 21 publications
(23 reference statements)
0
55
0
1
Order By: Relevance
“…Finally, five other core bacterial OTUs, previously referred to as 'Alpha-2.2' within the family Acetobacteraceae, had a positive associations with Crithidia infection. Although we categorized this group as core based on repeated retrieval from Apis and Bombus (Martinson et al, 2011;Moran et al, 2012), these bacteria are also common in nectar (Jojima et al, 2004) and solitary bees that otherwise lack core bacteria found in Apis and Bombus (Martinson et al, 2011;Koch et al, 2013). Therefore, these Acetobacteraceae OTUs may be repeatedly introduced from nectar, as suggested by studies on honey bees (Vojvodic et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, five other core bacterial OTUs, previously referred to as 'Alpha-2.2' within the family Acetobacteraceae, had a positive associations with Crithidia infection. Although we categorized this group as core based on repeated retrieval from Apis and Bombus (Martinson et al, 2011;Moran et al, 2012), these bacteria are also common in nectar (Jojima et al, 2004) and solitary bees that otherwise lack core bacteria found in Apis and Bombus (Martinson et al, 2011;Koch et al, 2013). Therefore, these Acetobacteraceae OTUs may be repeatedly introduced from nectar, as suggested by studies on honey bees (Vojvodic et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Kozakia Lisdiyanti et al 2002 was subsequently proposed as the sixth genus with a single species, Kozakia baliensis Lisdiyanti et al 2002(Lisdiyanti et al, 2002. Very recently, the seventh and the eighth genera were described: Saccharibacter Jojima et al 2004 and Swaminathania Loganathan and Nair 2004 with a single species each, Swaccharibacter floricola Jojima et al 2004 and Swaminathania salitolerans Loganathan andNair 2004, respectively (Jojima et al, 2004;Loganathan and Nair, 2004). Among the four genera mentioned above, the three genera, Asaia, Kozakia, and Swaminathania were related phylogenetically to each other.…”
Section: Introductionmentioning
confidence: 99%
“…agataea Yukphan et al 2011, Komagataeibacter Yamada et al 2013, and Nguyenibacter Vu et al 2013(Greenberg et al, 2006Jojima et al, 2004;Kersters et al, 2006;Lisdiyanti et al, 2002;Loganathan and Nair, 2004;Skerman et al, 1980;Urakami et al, 1989;Vu et al, 2013;Yamada and Yukphan, 2008;Yamada et al, 1997Yamada et al, , 2000Yamada et al, , 2012aYamashita et al, 2004;Yukphan et al, 2005Yukphan et al, , 2008Yukphan et al, , 2009Yukphan et al, , 2011.…”
Section: Vol 59 Malimas Et Almentioning
confidence: 99%